(untitled) (Bangladesh Journal of Medical Science, 2016)
Objective: The descriptive correlational study aimed to examine the relationships between organizational commitment, supervisory support, and job satisfaction in a public specialized hospital in Bangladesh. Method: Data were collected by using self-administered questionnaires from the random samples of 126 nurses. The questionnaires included organizational commitment questionnaire, supervisory support questionnaire and job satisfaction Survey. The validity of questionnaires was checked by five experts. The validity of the questionnaires on organizational commitment, supervisory support, and job satisfaction were 0.91, 0.85, and 0.89, respectively. The Cronbachs alpha coefficient of the questionnaires were 0.85, 0.85, and 0.82, respectively. Data were analyzed by using descriptive statistics and Pearsons product moment correlation statistics. Results: The result of the study showed that nurses perceived a moderate level of organizational commitment (M = 3.57, SD = 0.48), supervisory support (M = 3.9, SD = 0.48), and job satisfaction (M = 4.06, SD = 0.51). There was a moderate positive significant correlation between organizational commitment and job satisfaction (r = 0.32, p < 0.01) and moderate positive significant correlation between supervisory support and job satisfaction (r = 0.26, p < 0.01). Conclusion: The results of this study are helpful for nurse administrator to enhance job satisfaction in context of organizational commitment and supervisory support. Nurse administrator can apply study result to improve nursing knowledge in different aspect of their profession. It might be helpful to enhance the nurses job satisfaction in Bangladesh. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.39-43